Replacement-Value Accounting. - Rosen, L. S. (The Accounting Review, 1967)
Abstract The article examines various aspects of the concept of replacement value accounting. Replacement value theory is a particular measurement concept employed in ascertaining what constitutes that maintenance of a capital for the entire entity. Income is the residual that exists after capital is maintained in that sense dictated by this special measurement concept. In some cases it is possible that the capital to be maintained is measured in terms of current replacement costs. Historical cost accounting and the general or specific price level adjustments to it are restricted in the amount of their charges against revenue to the historical or price-level adjusted historical costs of those assets which the entity presently holds. In order to provide a detailed contrast with the price-level adjustments, it is necessary to leave the conceptual level of replacement-value accounting. However, whenever the individual-asset-and-liability-levels are selected for the purposes of brief comparisons, certain simplifying assumptions are required.